Withitness in the eLearning - Notar, Charles; Stefanie R. Sorbet, (Technium Social Sciences Journal, 2020)
The purpose of this article is to clearly define and exemplify "withitness," and determine can its value be in the eLearning education setting. The expert on classroom management, Jacob Kounin (8), listed four factors that underlie classroom management success. Foremost and first is “withitness,” which refers to the ability of a teacher to be perceptually and cognitively alert and aware of all parts of their classroom at all times. Withitness is key to classroom management! If you are an effective classroom teacher, how do you apply your classroom skillset of alertness and awareness to eLearning? How you do this in eLearning is the crux of this article. Withitness is awareness (presence), adroitness, clairvoyance, keenness, maximum engagement, perception, planned variety, rhythm learned through teaching, experience, vision, and wisdom. The article answers the question of implementing withitness in elearning by providing ways to attain the aspects of withitness in eLearning.